Photodissociation dynamics of formyl fluoride (HFCO) at 193 nm: Branching ratios and distributions of kinetic energy - Lee, SH; Wu, CY; Yang, SK; Lee, YP (My University, 2005)
Following photodissociation of formyl fluoride (HFCO) at 193 nm, we detected products with fragmentation translational spectroscopy utilizing a tunable vacuum ultraviolet beam from a synchrotron for ionization. Among three primary dissociation channels observed in this work, the F-elimination channel HFCO -> HCO+F dominates, with a branching ratio similar to 0.66 and an average release of kinetic energy similar to 55 kJ mol(-1); about 17% of HCO further decomposes to H+CO. The H-elimination channel HFCO -> FCO+H has a branching ratio similar to 0.28 and an average release of kinetic energy similar to 99 kJ mol(-1); about 21% of FCO further decomposes to F+CO. The F-elimination channel likely proceeds via the S-1 surface whereas the H-elimination channel proceeds via the T-1 surface; both channels exhibit moderate barriers for dissociation. The molecular HF-elimination channel HFCO -> HF+CO, correlating with the ground electronic surface, has a branching ratio of only similar to 0.06; the average translational release of 93 kJ mol(-1), similar to 15% of available energy, implies that the fragments are highly internally excited. Detailed mechanisms of photodissociation are discussed. (c) 2005 American Institute of Physics.